Evaluasi Tampilan Antarmuka Web SMK Komputama Menggunakan Metode Heuristik - Ariansyah, Awal; Bambang Sumantri, R Bagus (Jurnal Teknologi dan Bisnis, 2020)
Web is a digital page that functions to process and display information. A website has become an important element for an educational institution to disseminate information more widely and be known to more people. A web with a bad interface can cause user to have trouble finding the information they need and does not want to browse or visit again. Therefore, the appearance of a good and friendly interface with user is very important to be implemented in order to make user feel at home and comfortable in accessing related information. Evaluation of the appearance of the SMK Komputama web interface is carried out to produce recommendations for improving the appearance of a better interface based on ease of use (usability) so that operational activities on the web can run well. Evaluation was carried out using the heuristic method by 3 respondents using a questionnaire based on aspects of the heuristic method. There are 10 aspects of the heuristic method used namely feedback, matching, freedom, consistency, error, efficiency, recognition, design, diagnosis, and documentation. The results showed that the appearance of the SMK Komputama web interface had been quite good in terms of ease of use (usability) but there were still some interface points that needed to be improved.